Application of AHP and TOPSIS for the evaluation of Indian railway supply chain parameters (Indian Journal of Engineering and Materials Sciences (IJEMS), 2024)
Indian railways is a major public transportation system in India and one of the world’s largest and busiest rail networks. It is owned and run by the Indian government. This study presents an alternate method for assessing the entire operating performance of the Indian railway supply chain. To improve inventory control and customer service, we must examine how Indian railways operates from a supply chain standpoint. Indian railways benefits from the research as it makes it possible to categorize different government procurement-related difficulties. It examines inventory issues and provides recommendations for public procurement. As a result of this research, Indian railways decision-makers will be able to create an evaluation and relationship management model, allowing them to make procurement the main driver of their supply chain. We propose a supply chain model to evaluate service expectations and quality. We have identified various issues of the integration system, financial behavior, and management perspective related to supply chain management and analyzed various factors affecting availability, railway service quality, and reliability for effective supply chain management. The study employs the analytical hierarchy process (AHP), TOPSIS, and fuzzy rule base analysis.